Effectiveness Of An Ojs-Based Semester Lesson Plan Validation System: A User Experience Review - Safrizal Safrizal; Desri Jumiarti; Syamsul Bahri (Journal Emerging Technologies in Education, 2026)
Background. Quality assurance in higher education instructional planning is often hindered by inefficient validation processes for Semester Learning Plans (RPS). Digital innovations inspired by academic workflow systems offer potential solutions for improving efficiency and reliability in these processes. Purpose. This study aimed to evaluate the effectiveness and user experience of the RPS Validation and Evaluation System (SVeR), a digital platform modeled after the workflow of the Open Journal System (OJS). Specifically, it investigated whether SVeR could enhance the validation process and be positively received by lecturers. Method. Using an explanatory sequential mixed methods design, 17 lecturers from the PGMI Program at UIN Mahmud Yunus Batusangkar participated. The quantitative phase measured inter-rater reliability using Cohen's Kappa (?) statistics and assessed user perceptions through a rating questionnaire. The qualitative phase analyzed user feedback via thematic analysis. Results. Quantitative findings indicated a very high level of effectiveness, with an average Kappa coefficient of ? = 0.939, alongside a highly positive user acceptance, reflected in an average rating of 8.88 out of 10. Thematic analysis revealed three major advantages of SVeR: simplification of workflow, increased efficiency, and a positive impact on quality assurance. Conclusion. The study concludes that SVeR is both objectively effective and well-received by users, suggesting its potential as a model for digitalizing academic quality assurance processes in higher education.